2017
DOI: 10.1177/0363546517729152
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Therapy for Articular Cartilage Repair: Review of the Entity of Cell Populations Used and the Result of the Clinical Application of Each Entity

Abstract: Limited evidence is available regarding clinical benefit of stem cell therapy for articular cartilage repair. Because the literature contains substantial errors in describing the therapeutic cells used, researchers need to be alert and observant of proper terms, especially regarding whether the cells used were stem cells or cell populations containing a small portion of stem cells, to prevent confusion in understanding the results of a given stem cell-based therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 121 publications
(126 reference statements)
0
60
0
2
Order By: Relevance
“…Unlike "cultured stem cells," which are under strict regulation by regulatory authorities such as the US Food and Drug Administration for clinical application in most countries in the world, BMAC is categorized as "minimally manipulated cells" that are available for clinical application on the same day under the clinicians' responsibility in many countries. 4 Unlike the culture-expanded bone marrowederived MSCs, BMAC has a very low concentration of MSCs (0.001% to 0.01%). 2 The study by Cavinatto et al 1 confirmed that the cells present in BMAC did not meet the criteria to be characterized as MSCs according to the International Society for Cellular Therapy.…”
Section: See Related Article On Page 1860mentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike "cultured stem cells," which are under strict regulation by regulatory authorities such as the US Food and Drug Administration for clinical application in most countries in the world, BMAC is categorized as "minimally manipulated cells" that are available for clinical application on the same day under the clinicians' responsibility in many countries. 4 Unlike the culture-expanded bone marrowederived MSCs, BMAC has a very low concentration of MSCs (0.001% to 0.01%). 2 The study by Cavinatto et al 1 confirmed that the cells present in BMAC did not meet the criteria to be characterized as MSCs according to the International Society for Cellular Therapy.…”
Section: See Related Article On Page 1860mentioning
confidence: 99%
“…Recently, the nomenclature of the entity of cells used in stem cell therapy for the treatment of cartilage lesions has been emphasized to properly assess the efficacy and safety of various stem cell therapies. [4][5][6] The article by Cavinatto et al 1 clearly showed that the role of BMAC for the treatment of focal chondral lesions of the knee is still inconclusive based on the currently available data from translational and clinical studies. Although BMAC showed favorable outcomes for focal chondral lesions in some clinical studies, animal studies showed disparate outcomes.…”
Section: See Related Article On Page 1860mentioning
confidence: 99%
See 1 more Smart Citation
“…Hierzu sind die knorpelregenerativen Verfahren einschließlich der osteochondralen Transplantation, der autologen Chondrozytentransplantation und der Umstellungsosteotomien ein wichtiges Behandlungskonzept, um die Zahl der weiter zunehmenden endoprothetischen Eingriffe besonders auch in relativ jungen Jahren zu reduzieren. In Zukunft wird man möglicherweise neben den oben beschriebenen Verfahren zur Behandlung praearthrotischer und früharthrotischer Gelenke durch den Einsatz von autologen oder allogenen Stammzellaufbereitungen aus der Reihe des Binde-und Stützgewebes der Arthroseentwicklung noch besser entgegentreten können [58,59].…”
Section: Fa Zitunclassified
“…Depending on the autologous cartilage grafts, this solution significantly helps increase a large amount of chondrocytes at the cartilage damage site to facilitate the healing and repair process (Marlovits et al, 2006). Additionally, adipose tissue is known as the most suitable stem cell supplier as it can be collected easily from a liposuction procedure, which is considered to have the fewest ethical implications and increased donation (Miana and González, 2018;Park et al, 2018). Human adipose-derived stem cells (hADSCs) can be harvested in large amounts using established protocols.…”
Section: Introductionmentioning
confidence: 99%